(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
In basic education, Araling Panlipunan is integral in the formation among students, whom the government envisions to become citizens who are aware, actively involved in public and civic affairs, and contributing to the development of a progressive, just, and humane society. In the K-12 Program, the curriculum for grade 7 focused its study on Philippine History and Government. Its overall learning objective was to develop a keen understanding of the history and culture of the country, where students can convert these learning to real life by exercising creativity, critical thinking, problem-solving, and decision-making. The researchers utilized the unstructured interview and the questionnaire as a tool for cross-checking the respondents. They used adescriptive method which includes detailed factual information as it describes existing phenomena. The result of this research revealed that some teachers are upgraded and that schools should give more seminars workshops for teachers, provide and improve learning materials, and encourage extensive study. With constant addition and revision, the interpretation of these is often. Lastly, teachers should try something new in their classroom. The performance level of the respondents in Araling Panlipunan was measured according to the conducted final teacher-made tests. The respondents assessed the Araling Panlipunan Program in terms of objectives, instructional materials, techniques and strategies in teaching, evaluation materials, and quality of teachers. The new Araling Panlipunan curriculum under the K-12 program was in a modular instruction. Since its implementation in 2013 with the seventh-grade level, there has not been a systematic assessment to determine the effectiveness of modular instruction and to determine difficulties and concerns in carrying out the new curriculum. This study is an assessment of the Araling Panlipunan modules used in the seventh grade for the first and second grading periods. Assessments were carried out from the perspective of the experts in education, subject teachers, and seventh-grade students.